The association between papillary thyroid carcinoma and histologically proven Hashimoto's thyroiditis: a meta-analysis - Jeong Hyeon Lee; Younghye Kim; Jung-Woo Choi; Young‐Sik Kim (2012)
Objective No consensus exists on the association between papillary thyroid carcinoma (PTC) and Hashimoto's thyroiditis (HT). To resolve this controversy, this study aimed to evaluate the relationship between the two conditions using a meta-analysis. Methods We searched relevant published studies using citation databases including PubMed, Embase, and ISI Web of Science. The effect sizes of clinicopathologic parameters were calculated by odds ratio (OR), weighted mean difference, or hazard ratio (HR). The effect sizes were combined using a random-effects model. Results Thirty-eight eligible studies including 10 648 PTC cases were selected. Histologically proven HT was identified in 2471 (23.2%) PTCs. HT was more frequently observed in PTCs than in benign thyroid diseases and other carcinomas (OR=2.8 and 2.4; P <0.001). PTCs with coexisting HT were significantly related to female patients (OR=2.7; P <0.001), multifocal involvement (OR=1.5; P =0.010), no extrathyroidal extension (OR=1.3; P =0.002), and no lymph node metastasis (OR=1.3; P =0.041). Moreover, PTCs with HT were significantly associated with long recurrence-free survival (HR=0.6; P =0.001). Conclusions Our meta-analysis showed that PTC is significantly associated with pathologically confirmed HT. PTC patients with HT have favorable clinicopathologic characteristics compared with PTCs without HT. However, patients with HT need to be carefully monitored for the development of PTC.